Implikasi Jarak Rumah ke Sekolah Terhadap Motivasi Belajar Siswa - Bangun, Devi Permata Br.; Sihombing, Eka Putriani; Nababan, Iwain Oktaviona; Simanullang, Seevaira Chyta; Yunita, Sri (Indo-MathEdu Intellectuals Journal, 2024)
Students who have high motivation to learn will be more active in learning and strive to achieve optimal achievements. On the other hand, students who have low motivation to learn tend to be lazy to study and not enthusiastic about participating in learning. This study aims to analyze the implications of students' home distance to school on students' learning motivation. The research method used by the author, namely literature study, is a research method that uses literature sources such as books, journals, articles, and research reports to collect data and information to answer research questions. The research method used by the author, namely literature study, is a research method that uses literature sources such as books, journals, articles, and research reports to collect data and information to answer research questions. The main source of data for this research is scientific articles published in various journals and indexed by google scholar. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the analysis are known that the distance from students' homes to schools certainly affects students' motivation to learn, therefore there are several actions that can be taken so that it can help students have a spirit of learning and the distance from their homes to school is not a barrier for them to learn and of course have high motivation to learn.